Analyzing the Implementation of Educational Program Evaluation in Improving the Quality of Learning in Islamic Educational Institutions - Devinta Eka Sari; Rusdiana Navlia (Al-Alim: Jurnal Pendidikan Agama Islam, 2025)
The implementation of this educational program is very influential in improving the quality of learning in Islamic education. Because one of the educational problems faced by the Indonesian nation is the low quality of education at every level and educational unit. The method in this study uses the library method. The results of this study are that there are three evaluation models that can be applied to improve the quality of learning in educational institutions, the first is the Goal Oriented Evaluation Model (Goal-Oriented Evaluation Model). This model is the model that appeared the earliest, the second is the evaluation that fits the goal, the third is the "evaluation apart from the goal" model, Michael Scriven also developed another model, namely the formative summative model, and the last is this evaluation model emphasizes the operational aspects of description and assessment which are divided into 3 (three) evaluation phases, namely: preparation Antecedents, Process / Transaction Process / Transaction and Output / Results Output / Outcomes.